The effect of fuel injection pressure and combustion chamber configuration on fuel spray, combustion and emissions of a direct injection diesel engine: a CFD approach. Issue 1 (31st December 2022) - Khan, Shahanwaz; Panua, Rajsekhar; Bose, Probir Kumar
Abstract : In the present study, the combined impacts of injection pressure and piston bowl configuration on fuel–air mixing, combustion and emissions of a diesel engine have been analysed numerically. An investigation has been conducted at four different fuel injection pressures and three different combustion chamber configurations for the same bowl volume to have a constant compression ratio. The in-cylinder transient flow and subsequent turbulent combustion process have been modelled using computational fluid dynamics code AVL FIRE. The predicted results indicate that the brake-specific fuel consumption (BSFC) is decreased by 4.19%, 8.96% and 11.92% for HCC, 5.77%, 9.92% and 13.68% for CCC, and 5.13%, 9.19% and 12.92% for TRCC when engine operates with an injection pressure of 215, 230 and 250 bar, respectively compared to 200 bar at full load operation. Soot emissions for CCC and TRCC engines are decreased by 23.4% and 33.43%, respectively, compared to baseline HCC engines.